Hubungan Intensitas Kebisingan, Umur dan Masa Kerja dengan Gangguan Non-Auditory (Fisiologis, Psikologis dan Komunikasi) pada Nelayan di Desa Bogak Kabupaten Batubara - Rahmadillah, Al Fiza Putri; Arrazy, Syafran; Siregar, Putra Apriadi (Puslitbang Sinergis Asa Professional, 2024)
Fishermen's lack of awareness regarding the use of ear protection equipment, and prolonged exposure that exceeds working time, as well as the danger of noise intensity exceeding the threshold value originating from fishing boat engines, can have an impact on fishermen's physiological, psychological and communication disorders. The aim of this research is to determine the relationship between noise intensity, age, length of service, length of exposure and use of ear protective equipment (APT) with non-auditory disturbances experienced by fishermen in Bogak Village, Batubara Regency. The research method uses quantitative research with a cross-sectional design. The population in this study was 105 people. The sampling technique used simple random sampling with the lemeshow formula, so the research sample consisted of 81 respondents. The research instrument uses a questionnaire and a sound level meter (SLM) to measure noise intensity. Data analysis used the chi square test, but if it did not meet the requirements, the Fisher Exact test was used. The results of the study showed that there was a relationship between noise intensity, age and years of work with non-auditory disorders. Noise intensity has a p value of 0.001, age has a p value of 0.002, and years of service has a p value of 0.009. Duration of exposure and use of ear protective equipment (APT) could not be subjected to bivariate analysis because the data were homogeneous. The research conclusion shows that there is a relationship between noise intensity, age and years of work with non-hearing disorders in fishermen in Bogak Village, Batubara Regency. Suggestions for future researchers to conduct research with other related variables and provide education to fishermen about the dangers of noise intensity that exceeds the threshold value for fishermen's health and the importance of using ear protection when working.